Nano layers in the bismuth telluride semiconductive alloys that are used in nano satellites - Piskin, Mehmet Burcin; Derun, Emek Moroydor (IEEE, 2007)
The level-to-level and island growth of nanolayers: copper, nickel and boron realizes spontaneously between the layers Te-1-Te-1 in the process of the directed crystallization of bismuth telluride (doped by easily diffusing impurities). This was proved by the electron-microscopic photos of the chipped surface (0001) Bi2Te3 , Bi2Te3 and Bi2Te3 . The wide set of island sizes 50-200 nm was revealed. The appearance nature of nano-layers, islands and their enlargement in the interlaminar space of the layered crystal of bismuth telluride is the same as on the open surfaces of the systems semiconductor-metal. The two-dimensional islands, which combining form the wetting layer of nano-thickness appear on the initial steps of the growth. It is established, that the copper layers, nano-sized by the height, are charged with extremal behavior of Hall thermoelectromotive force and other kinetic parameters Bi2Te3 . The temperature dependencies of coefficients of Hall, electroconductivity, mobility and other kinetic parameters revealed the oscillation character. These extremums can be connected with the consecution of the phase transfers, known as order-disorder transfers, connected with positional order. The anomal increase of the mobility of the charge carriers (more, than in 5 times) in the direction along axes of the (0001) Bi2Te3 layers at the temperature 105K is observed so it will be a great improvement that can be used in nano satellites.
Keywords: Engineering; Remote Sensing